Terror Trap - Onyearugbulem, Chinyere (Evans Brothers (Nigeria Publishers) Ltd, 1999)
It began as a mystery but ended uo as a murder! Edger, Daisy's step-brother, is playing a game with an anonymous caller while his parents are not around. When the caller realizes that Daisy Sleigh is a detective, he changes his schemes and starts keeping Daisy busy. Daisy wants to take it easy, but when she does not follow his order, a child is killed; and so Daisy is stuck in the mud...
Keywords: Juvenile Fiction